Perancangan Model Supervisi Pendidikan Islam dalam Meningkatkan Mutu Pembelajaran Pendidikan Agama Islam - Vian Widiyanto; Rudi Hermawan; Meti Fatimah (Lembaga Yasin AlSys, 2026)
Educational supervision is a strategic instrument for improving the quality of Islamic Religious Education (PAI) instruction. However, its implementation in various educational institutions remains predominantly oriented toward administrative and evaluative aspects and therefore does not yet fully support teachers’ comprehensive professional development. Moreover, existing supervision models generally adopt modern theories without systematically integrating Islamic values as their philosophical and operational foundations. This study aims to design the Integrative Islamic Educational Supervision Model (MSPI), which combines modern educational supervision theory with perspectives from the Qur’an, hadith, and the thoughts of Islamic education figures to improve the quality of PAI instruction. The study employed a qualitative approach using the literature research method through content analysis and conceptual synthesis of literature on educational supervision, Islamic educational management, instructional leadership, and the thoughts of Islamic education figures. The results produced the MSPI, which consists of four main components: normative and philosophical foundations; fundamental supervision values encompassing tawhid, amanah, ihsan, shura, justice, uswah hasanah, ta‘awun, and istiqamah; a supervision process comprising needs analysis, planning, observation, reflection, coaching, mentoring, spiritual development, evaluation, and follow-up; and outputs and impacts oriented toward improving teacher competence, strengthening an Islamic quality culture, and enhancing the quality of PAI instruction. This study concludes that the integration of modern supervision theory and the Islamic education paradigm produces a holistic supervision model, such that supervision functions not only as a mechanism for academic oversight but also as a continuous process of professional, spiritual, moral, and social development. The novelty of this study lies in the formulation of an integrative supervision framework that can serve as a conceptual and operational foundation for developing PAI supervision practices in Islamic educational institutions.